THE INFLUENCE OF FRONTLOADING STRATEGY TOWARD STUDENTS’ LISTENING COMPREHENSION - Zuhriyah, Mukminatus (English Department, University of Riau Kepulauan, Batam,Indonesia, 2020)
All English departments provide the listening courses that must be studied by their students. In fact, the students often find difficulties in understanding the listening texts so that their listening comprehension becomes low. This condition also happens to the students of English department of UNHASY. One of the causes of it is the teaching strategy for listening which is not appropriate. Therefore, the researcher implemented frontloading strategy for teaching listening in this study. The purpose of this study was to know whether or not frontloading strategy influenced the students’ listening comprehension. The research method used was quasi experiment with the design of pretest posttest nonequivalent control group. The population and the sample of the research were the two classes of the second semester students of English education department of UNHASY in the academic year of 2018/2019. After the implementation of frontloading strategy in experimental class and direst listening in control class, the students’ post listening comprehensions were compared by using independent sample t-test whose result was that sig. (2-tailed) (0.004) was lower than 0.05. In short, it is concluded that frontloading strategy influences students’ listening comprehension.